"The Chinese Dream" and Chinese Foreign and Security Policies—Rosy Rhetoric versus Harsh Realities. (2nd July 2016) - Berkofsky, Axel
Abstract : The "China Dream" announced by Chinese President Xi Jinping' in 2012 paints a very rosy picture of China under his seemingly undisputed leadership: China's economic and political rise will be beneficial to China and indeed the international community putting Beijing on top of the list of "peace-loving" countries. Reality, however, as it turned out over the last four years, is distinctively different as a number of countries in China's neighborhood and beyond can surely confirm. Indeed, Beijing unilaterally claiming and building civilian and military facilities on disputed islands in the South China Sea are arguably the very opposite of a peaceful contribution to world politics and security facilitated by the rhetorical hype of Xi's "Chinese Dream." While outside observers can be excused for concluding that the "Chinese Dream" mantra is directed at the Chinese domestic audience to distract from the very many economic, environment and social problems within China, the consequences of Beijing's "dreaming" of re-gaining its former undisputed "Middle Kingdom" status in Asia are very much felt abroad. This, it is argued, could be the time when "dreams" turn into "nightmares" for those at the receiving end of Beijing's dream.